Latest clinical evidence and further development of PARP inhibitors in ovarian cancer. (10th May 2018) - Mirza, M R; Pignata, S; Ledermann, J A
Abstract: For several decades, the systemic treatment of ovarian cancer has involved chemotherapy, with the relatively recent addition of antiangiogenic strategies given with chemotherapy and in the maintenance setting. In the past decade, numerous poly(ADP-ribose) polymerase (PARP)-inhibiting agents have been assessed. We review key trials that have led to the approval of three PARP inhibitors—olaparib, niraparib and rucaparib—as maintenance therapy for platinum-sensitive recurrent ovarian cancer. We discuss the efficacy and safety of these agents in the populations studied in clinical trials. We then provide an overview of the numerous avenues of ongoing research for PARP inhibitors in different treatment settings: as treatment rather than maintenance strategies and in combination with other anticancer approaches, including antiangiogenic and immunotherapeutic agents. Three phase III trials (NOVA, SOLO2 and ARIEL3) demonstrated remarkable improvement in progression-free survival (PFS) with PARP inhibitors given as maintenance therapy in patients with complete or partial response after platinum-based therapy for platinum-sensitive ovarian cancer. Differences in trial design and patient populations influence the conclusions that can be drawn from these trials. Overall survival data are pending and there is a limited experience regarding long-term safety. PARP inhibitors have transformed the management of ovarian cancer and have changed the course of disease for many patients. Although recent approvals are irrespective of BRCA mutation or homologous repair deficiency status, genetic profiles, as well as dosing schedules, tolerability and affordability, may influence patient selection and the setting in which PARP inhibitors are used. The development and evolution of PARP inhibitors continue, with new agents, strategies, combinations and indications under intensive evaluation.